Nano-Hydroxyapatite Isolation and Characterisation of Echinometra mathaei from the Persian Gulf - Ali Rajabiyan; Luigi Vaccaro; Amanollah Zarei Ahmady (Tropical Life Sciences Research, 2023)
The study focuses on the preparation and characterisation (physicochemical and mechanical) of hydroxyapatite [Ca10(PO4)6(OH)2] (HA) from sea urchin, Echinometra mathaei. Therefore, nano-sized HA prepared from sea urchin shells were collected from beaches of the Persian Gulf in Iran. Sea urchin shells were found a source of calcium carbonate in the form of aragonite (calcite) that crystallised in an organic matrix. HA is one of the polymers used in coating the nanoparticles extracted from various sources. The calcined aragonite converted to nanosized hydroxyapatite powder by chemical reaction with orthophosphoric acid while maintaining stoichiometry, Ca/P = 1.667 at 80°C. To determine the purity of the nano-hydroxyapatite (nHA) numerous analytical procedures were used. Fourier transforms infrared spectroscopy (FTIR) confirmed the presence of the peak of 961 cm-1 is related to the symmetric tensile band of the P-O bond, and the peak of 1038 cm-1 and 1091 cm-1 is related to the tensile solid absorption of the PO4 as functional groups of nHA. The nanocrystalline HA can be observed from the SEM images. Thermogravimetric analysis (TGA-DTA) demonstrates the thermal stability of nHA powder. The results show successful isolation and characterisation study of this crucial nano-material shows it is valuable in biomedical applications, particularly in bone tissue engineering. Indeed, its fabrication is easy and economical.